Perbandingan Penggunaan Kata Ganti Orang dalam Bahasa Mandarin dan Bahasa Indonesia - siswanlie, Cindy Siswanlie; tjong, Dewi Kartika; Hualangi, Anthony; Anwar, Sinar; Agustina, Tiurmaya (Universitas Muhammadiyah Tapanuli Selatan, 2025)
Personal pronouns are one of the most commonly used grammar. In Mandarin and Indonesian, there are both personal pronouns. However, because Mandarin and Indonesian come from different families, there are certainly similarities and differences in personal pronouns in the two languages. Based on this background, this study aims to describe and explain these similarities and differences. To achieve this goal, the researcher used a qualitative descriptive research method, namely by describing and explaining the similarities and differences between personal pronouns in Mandarin and Indonesian. The data collection technique used was a literature study, where the data was obtained from books related to personal pronouns in Mandarin and Indonesian. From the results of the data analysis, it was found that there were three similarities and six differences. These similarities and differences are seen in terms of the division of types, usage and position of placement in sentences.